1996
DOI: 10.1590/s0074-02761996000100025
|View full text |Cite
|
Sign up to set email alerts
|

Feeding preference of the larvae of Chrysomya megacephala (Fabricius) (Diptera: Calliphoridae) and Ravinia belforti (Prado e Fonseca) (Diptera: Sarcophagidae) concerning different diets

Abstract: tion, two with the 4th, three with the 5th, and one with the 6th generation).The tests were done in a 15cm diameter Petri dish containing a layer of 1cm of pure agar (2g for 20ml of water) so the larvae could move. Nine 2cm circular holes, were opened in the agar eight being equally distant from the central hole ( Fig.). We dropped melted agar in the newly opened holes, which after getting cold, formed a thin layer that sealed the space between the glass and the agar. Thus, preventing the larvae from escaping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…A disease-causing filth fly that is not attracted to human food as well as to potential reservoirs of pathogens is unlikely to represent much of a threat in terms of (Hall, 1948;Bohart and Gressitt, 1951;Greenberg, 1973;Skidmore, 1985;Daniel et al, 1989). Most of these flies are also attracted to seafood and fisheries products (Bohart and Gressitt, 1951;Okaeme, 1986;Walker and Donegan, 1988;Haines and Rees, 1989;Olsen and Sidebottom, 1990;Esser, 1990Esser, , 1991Olsen et al, 1992;d'Almeida and de Mello, 1996;d'Almeida and Salviano, 1996). Many have been isolated from foods examined by FDA scientists (Hamm and Olsen, 1979;Olsen, 1988;Olsen et al, 1993;Olsen, 1996).…”
Section: Interpreting the Bionomic Datamentioning
confidence: 99%
“…A disease-causing filth fly that is not attracted to human food as well as to potential reservoirs of pathogens is unlikely to represent much of a threat in terms of (Hall, 1948;Bohart and Gressitt, 1951;Greenberg, 1973;Skidmore, 1985;Daniel et al, 1989). Most of these flies are also attracted to seafood and fisheries products (Bohart and Gressitt, 1951;Okaeme, 1986;Walker and Donegan, 1988;Haines and Rees, 1989;Olsen and Sidebottom, 1990;Esser, 1990Esser, , 1991Olsen et al, 1992;d'Almeida and de Mello, 1996;d'Almeida and Salviano, 1996). Many have been isolated from foods examined by FDA scientists (Hamm and Olsen, 1979;Olsen, 1988;Olsen et al, 1993;Olsen, 1996).…”
Section: Interpreting the Bionomic Datamentioning
confidence: 99%
“…preferred faeces as collection substrate. D'Almeida and Barbosa (1996) reported that, mashed fish was a highly attractant diet to the larvae of the sarcophagid fly Ravinia belforti (Prado & Fonseca, 1932).…”
Section: Discussionmentioning
confidence: 99%
“…Apesar disso, estudos sobre biologia (Oliveira-da-Silva et al 2006), ecologia (Almeida & Salviano 1996) e sucessão (Barros et al 2008) em carcaças de animais dos Sarcophagidae ainda são raros. Um dos fatores limitantes é a diagnose complicada das espécies, pois é baseada majoritariamente em caracteres da terminália dos machos, enquanto chaves para fêmeas são raras (Vairo et al 2011(Vairo et al , 2015a.…”
Section: Sarcophagidaeunclassified